"Kataa ou-Outa", Mi'ira", "Jieyuu-Wuchiirua" (Wayuunaiki, Spanish, English) - Apüshana, Vito; Gill, Trans. Rosalind (Tusaaji: A Translation Review, 2020)
Poems written in Wayuunaiki and Spanish, translated into English.